2012
DOI: 10.1007/s12550-012-0148-5
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Aspergillus section Flavi and aflatoxin B1 in brewer’s grain used as pig feedstuff in Córdoba, Argentina

Abstract: Brewing industry by-products are important animal feedstuff alternatives for local swine producers in Córdoba, Argentina. The high content of nutrients makes these by-products vulnerable to bacterial and fungal contamination. The objectives of the present study were (1) to determine the presence of Aspergillus section Flavi in brewer's grain used to feed pigs and (2) to evaluate the incidence of aflatoxin B(1) in the substrate. Total fungal count of most samples exceeded the levels proposed as feed quality lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…Previous studies carried out by our research group demonstrated the humid and acidic conditions of this alternative feedstuff for swine production (Asurmendi et al, 2013(Asurmendi et al, , 2014. Such conditions could allow the development of L. monocytogenes since this microorganism is well known for its resistance to different environmental conditions, including acid pH, high NaCl concentration, microaerophilia and refrigeration temperatures (Dimitrijevic et al, 2006;Ivy et al, 2012;Jeyaletchumi et al, 2010).…”
Section: Introductionmentioning
confidence: 78%
“…Previous studies carried out by our research group demonstrated the humid and acidic conditions of this alternative feedstuff for swine production (Asurmendi et al, 2013(Asurmendi et al, , 2014. Such conditions could allow the development of L. monocytogenes since this microorganism is well known for its resistance to different environmental conditions, including acid pH, high NaCl concentration, microaerophilia and refrigeration temperatures (Dimitrijevic et al, 2006;Ivy et al, 2012;Jeyaletchumi et al, 2010).…”
Section: Introductionmentioning
confidence: 78%
“…High contamination of swine feed has been well documented (Kabak et al, 2007;Simas et al, 2007;Pereyra et al, 2011;Gerbaldo et al, 2011;Gowda et al, 2013;Asurmendi et al, 2013). This may result in direct exposure of workers when they handle the feed that is given to the animals.…”
Section: S Viegas Et Almentioning
confidence: 99%
“…Bacteria are capable of producing compounds that could either repress pathogenesis by inhibiting filamentation or enhance fungal virulence determinants [5]. Co-existence of two major pathogens, such as Aspergillus flavus and Listeria monocytogenes, has been reported in food systems such as dairy products, eggs, meats, and brewer's grain [6][7][8][9][10]. The interactions between those two pathogens are critical in shaping the food microbial communities and exert a significant impact on the colonization, survival and even pathogenesis of these microorganisms.…”
Section: Introductionmentioning
confidence: 99%